Evaluation of three-dimensional deformation fields of the Earth by methods of the projective differential geometry. Rigid rotations of the Earth - Tadyeyev, O. A. (Видавництво Львівської політехніки, 2016)
Aim. The aim is this research is the evaluation of the Earth’s rigid rotation as a component of global deformation fields in interconnection with angular distortions of the geocentric spatial coordinate system. Methodology. Solutions will be achieved by methods of projective differential (metric) geometry based on the differential presentation of transformations of Riemannian space images in the form of its complicated diffeomorphic manifolds. Based on the essence of the International Terrestrial Reference System (ITRS).in which the input data are given, and on a global scale the deformation fields, as a Riemannian manifold it is defined as a the tangent of Euclidean space. To solve the problem are used the methods of description the change of the Riemannian metric in the tangent Euclidean space, is parameterized by the Cartesian coordinate system. Results. The basis of the methods used enabled the results, which are the terms of its content. The practical application has a dual interpretation. In the former , an expression of angular distortions for needs of the deformation analysis is derived from formulas for angles of the rigid Earth's rotation into projections on ITRS coordinate planes. At the same time, it is proven that these angles are indicators of the coordinate system distortion. The hypothesis of probable deformations of the spatial geocentric coordinate system is substantiated by the geophysical content of the ITRS concept. The identity of conditions of the Earth's parameterization by ITRS and of the tangent Euclidean space parameterization by the Cartesian coordinate system has been proven. On this basis, the truthfulness of the hypothesis can be verified by empirical values of angles that are defined from results of GNSS-observations. In this case of significant importance, they are indicators of angular distortions of the ITRS system or an expression by deviations from the axes orthogonality in its ITRF version as measures of the oblique-angled Cartesian system into the any epoch of observation that follows. Using methods of projective differential geometry the formulas are obtained for the coordinate axes directions of the deformed system. Scientific novelty. It is proven that the approach for solving the problem of the deformation analysis in geodynamics based on the Riemannian geometry it is generalizing relative to its use. On this basis, prospects for filing of deformation fields by nonlinear functional models are substantiated. Practical significance. The obtained results are designed to be used for the evaluation of global deformation fields of the Earth and solving problems of the modern geodesy in its interconnection with geodynamics in the context of reference frame research. All analytical expression of angular distortions is given in general form, which is able to transfer the nonlinear deformation tendencies. A methodology of the deformation analysis is adapted to be used as input data for the results of the Global Navigation Satellite System (GNSS) monitoring station coordinates, taking into account the probable ITRS angular distortions. Мета. Оцінювання жорсткого обертання Землі як складової глобальних деформаційних полів у взаємозв’язку з кутовими спотвореннями геоцентричної просторової системи координат. Методика. Розв’язки досягнуто методами проективно-диференціальної (метричної) геометрії на основі диференціального подання перетворень образів ріманового простору у формі його складних диффеоморфних многовидів. Враховуючи сутність системи ГЛ^Б, у якій задано вхідні дані, та глобальний масштаб деформаційних полів, рімановим многовидом визначено дотичний евютідовий простір. Щоб виконати завдання, використано прийоми описування змін ріманової метрики у дотичному евклідовому просторі, який параметризований декартовою системою координат. Результати. Використовувана основа дала змогу одержати результати, які з погляду їх змісту і практичного застосування мають двояку інтерпретацію. У частині вираження групи параметрів кутових спотворень для потреб деформаційного аналізу встановлено співвідношення для кутів жорсткого обертання Землі в проекціях на координатні площини системи ITRS. Водночас доведено, що ці кути є показниками спотворень системи координат. Гіпотеза ймовірних деформацій геоцентричної просторової системи обгрунтована геофізичним змістом концепції створення ITRS. Аргументовано тотожність умов параметризапії Землі системою ITRS і параметризанії дотичного евютідового простору декартовою системою координат. На цій основі істинність гіпотези можна перевірити за емпіричними значеннями кутів, які визначені з результатів GNSS-спостережень. За умови достатньої значущості, вони є показниками кутових спотворень системи ITRS чи, у вираженні відхиленнями від ортогональності осей у ITRF-реалізації, мірами косокутної декартової системи на будь-яку епоху спостережень після реалізації. Методами проективно-диференціальної геометрії одержано аналітичні вираження напрямів координатних осей деформованої системи. Наукова новизна. Доведено, що підхід до розв’язання задач деформаційного аналізу в геодинаміці на засадах ріманової геометрії є узагальнювальним відносно використовуваного. На такій основі обгрунтовано перспективи подання деформаційних полів нелінійними функціональними моделями. Практична значущість. Одержані результати спрямовані на їх використання під час оцінювання глобальних деформаційних полів Землі та вирішення питань сучасної геодезії в її взаємозв’язку з геодинамікою на основі досліджень референцних систем координат. Усі аналітичні вираження показників кутових спотворень подано у загальному вигляді, який здатний передати нелінійні закономірності деформації. Методика деформаційного аналізу адаптована до використання вхідними даними результатів GNSS-моніторингу координат станцій з урахуванням деформації системи ITRS.
Оцінювання тривимірних деформаційних полів землі методами проективно-диференціальної геометрії. Жорсткі обертання Землі
Keywords: Riemannian diffeomorphic manifolds; space metric tensor; deformation analysis; rigid rotation of the Earth; deformation of the coordinate system; ріманові диффеоморфні многовиди; метричний тензор простору; деформаційний аналіз; жорсткі обертанім Землі; деформація системи координат